2017
DOI: 10.1002/jnr.24202
|View full text |Cite
|
Sign up to set email alerts
|

Converging early responses to brain injury pave the road to epileptogenesis

Abstract: Epilepsy, characterized by recurrent seizures and abnormal electrical activity in the brain, is one of the most prevalent brain disorders. Over two million people in the United States have been diagnosed with epilepsy and 3% of the general population will be diagnosed with it at some point in their lives. While most developmental epilepsies occur due to genetic predisposition, a class of "acquired" epilepsies results from a variety of brain insults. A leading etiological factor for epilepsy that is currently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 117 publications
(182 reference statements)
0
33
0
Order By: Relevance
“…In 30-to 40-hour simultaneous video and surface EEG recordings from rats 12 to 15 weeks after sham or FPI, none of the sham rats (n = 9) showed electrographic seizures, but spontaneous electrographic and behavioral seizures were observed in 8 of 13 FPI rats (~62%; Fig 4). In rats with spontaneous seizures, the average seizure severity was Racine score 3.37 AE 0.18 (range, [3][4], and average seizure duration was 97.88 AE 10.20 seconds (range, 50-140 seconds), confirming the risk for post-traumatic epileptogenesis in the experimental model. It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, 40 implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies.…”
Section: Systemic Tlr4 Antagonism In Vivo Has Opposing Effects On Earmentioning
confidence: 71%
See 3 more Smart Citations
“…In 30-to 40-hour simultaneous video and surface EEG recordings from rats 12 to 15 weeks after sham or FPI, none of the sham rats (n = 9) showed electrographic seizures, but spontaneous electrographic and behavioral seizures were observed in 8 of 13 FPI rats (~62%; Fig 4). In rats with spontaneous seizures, the average seizure severity was Racine score 3.37 AE 0.18 (range, [3][4], and average seizure duration was 97.88 AE 10.20 seconds (range, 50-140 seconds), confirming the risk for post-traumatic epileptogenesis in the experimental model. It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, 40 implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies.…”
Section: Systemic Tlr4 Antagonism In Vivo Has Opposing Effects On Earmentioning
confidence: 71%
“…Although early increases in dentate excitability after brain injury have been proposed to contribute to epileptogenesis, a convincing demonstration of a causal association has been lacking. We recently showed that suppressing post‐traumatic increases in neurogenesis reduced dentate excitability and epileptogenesis in parallel, supporting the association between excitability and epileptogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of glial inflammatory signals including TNFα and purinergic receptors have been shown to impact synaptic plasticity and hippocampal memory function (Beattie et al, 2002;Belarbi et al, 2012;Pascual et al, 2012;Pribiag and Stellwagen, 2014). Increases in neuronal excitability and immune activation are hallmarks of traumatic brain injury and present a condition in which neuroimmune interactions are potentially accentuated (Chiu et al, 2016;Neuberger et al, 2017a). While post-traumatic inflammatory responses are implicated in neurodegeneration, and immunosuppressants can improve neurological outcomes after brain injury (Saletti et al, 2019), mechanisms underlying immune regulation of neuronal function and behaviors are not fully understood.…”
Section: Introductionmentioning
confidence: 99%